Characterizing the topology dynamics in mobile ad hoc networks:modeling and analyzing techniques using the queuing theory - QIN Guang-cheng1; YANG Pan-long2; TIAN Chang2; CHEN Qiang3; YIN Hao3 (Tongxin xuebao)
A new modeling parameter named link broken rate（LBR） was proposed so as to characterize the topology dy-namics.On the basis of the definition of the network dynamic characteristics parameter LBR,the expectations of the time interval between the links broken was use to measure the LBR,and a cyclic queuing model was created to analyze the characteristic of dynamic link and an analytic expression was derived.Employing the commercial simulation platform Qualnet,simulations were carried out and the model was reasonable evaluated.And the further simulation results show that,the network dynamic performance are highly related to the LBR,and the dynamic link model can integrate the mo-bility velocity,node density,and transmission range efficiently,which essentially characterize the network,and could provide theoretical results for analysis and simulation works on network dynamics.